Clinoidal Meningioma associated with an Anterior communicating Artery Aneurysm : Case Report - Sharma, Rajan Kumar; Jha, Rajeev; Bista, Prakash (Nepal Journal of Neuroscience, 2019)
Coexistence of primary brain neoplasm’s with intracranial aneurysms is rare but presents a diagnostic and therapeutic challenge to healthcare providers. We describe the case of a 46-year-old lady who had an anterior communicating aneurysm with a small left clinoidal meningioma. The meningioma was an unexpected finding encountered during the surgery for aneurysmal clipping. Both the lesions were dealt with simultaneously.